Predictors of Bribe-Taking: The Role of Bribe Size and Personality - Vranka, Marek A.; Bahník, Štěpán (Frontiers in Psychology, 2018)
Laboratory studies allow for studying predictors of bribe taking in a controlled setting. However, the existing laboratory tasks often lack any connection to norm violation or invite participants to role-play. Using a new experimental task for studying the decision to take a bribe, which overcomes the problems mentioned above by embedding the opportunity for bribe taking in an unrelated task that participants perform, we found that refraining from harming a third party by taking a bribe was associated with lower bribes and higher scores on the honesty-humility scale from the HEXACO personality inventory. Trial-level analysis showed that response times were longer for trials with bribes and even longer for trials in which bribes were accepted. These results suggest that taking a bribe may require overcoming the default honest response and support validity of the honesty-humility scale in predicting moral behavior.